The Role of Accounting and Internal Control in Reducing Bureaucracy in the Public Sector - Ionescu, Luminita (Journal of Economic Development, Environment and People, 2016)
The aim of this paper is to present the relation between efficient internal control and accounting procedures and how the internal control system could play an important role in reducing bureaucracy. Nowadays, the government accounting and control of public finances are a national and international priority, in the context refugee crisis and terrorist attacks. Modernization of the public sector accounting could accelerate the process of reducing bureaucracy by implementing accounting information system and electronic signature. The reform of the public administration in all European countries developed new control techniques and procedures in order to control public sector budget and financial activity. Efficient intern control procedure and managerial responsibility could contribute to good governance, transparency and low level of bureaucracy.